Linking education and health data to examine the characteristics of children prescribed antipsychotic medication.: IJPDS (2017) Issue 1, Vol 1:042, Proceedings of the IPDLN Conference (August 2016) - Brophy, Sinead; Kennedy, Jonathan; Fernandez-Gutierrez, Fabiola; John, Ann; Potter, Robert; Christine, Linehan; Kerr, Michael (International Journal of Population Data Science, 2017)
ABSTRACT Objectives To examine the characteristics of children who are prescribed antipsychotic medication. Approach A cohort study using routine data from general practitioner and hospital records linked with education records. All children in Wales between the years 1999 to 2014 were included in the analysis, demographic characteristics and outcomes of children were stratified by intellectual disability/autism (identified using education records and GP records) and antipsychotic use. All data were linked and held in the Secure Anonymised Information Linkage (SAIL) Databank in Wales Results Of children with intellectual disability 2.4 % (360/14428) have been prescribed an antipsychotic and 75 % of these have a diagnosis of autism. This compares with 0.19% (1126/602320) of children without intellectual disability who are prescribed an antipsychotic. Children, predominantly boys (78.1% (281/360) of those with intellectual disability prescribed an antipsychotic were boys compared to 67.12% (9442/14068) of those not prescribed antipsychotics), with aggression codes (17.5% of those on an antipsychotic had aggression codes compared to 1.36% of those without antipsychotic) were more likely to be prescribed antipsychotics. Those with intellectual disabilities were prescribed antipsychotics at a younger age (58 % of those with intellectual disability started the drug before the age of 14 compared to 29 % of those without intellectual disability) but were less likely to be from a deprived area compared to those prescribed antipsychotics but without intellectual disability/autism (22.5 % and 28.4 %, were in the lowest fifth of deprivation, intellectual disability and non- intellectual disability, respectively). Antipsychotic use was associated with more visits to the GP for epilepsy, diabetes and injury (post drug compared to prior to drug) and higher deaths in childhood (compared to those not give antipsychotics). Conclusions The linkage of the education records allowed intellectual disability to be used as an explanatory factor in analysis looking at drug prescriptions. The majority of children prescribed antipsychotics do not have psychotic or mental disorder diagnosis codes but have a diagnosis of behavioural problems, attend special schools and have intellectual difficulties. In the group with intellectual disability/autism there is evidence that the use of antipsychotics may be associated with more visits to the GP for epilepsy, diabetes, injury (post drug compared to prior to drug) and is associated with more deaths in childhood. These findings support concerns that antipsychotics may be over used for managing predominately behavioural problems.